Incidence and importance of reflux in testicular veins of healthy men evaluated with color duplex sonography - Kocakoc, E; Kiris, A; Orhan, I; Bozgeyik, Z; Kanbay, M; Ogur, E (John Wiley & Sons Inc, 2002)
Purpose. Reflux in the testicular veins plays a crucial role in the diagnosis of a varicocele. The aim of this study was to evaluate the incidence and the sonographic features-duration and velocity-of reflux in testicular veins of healthy men using color duplex sonography (CDS). Methods. Healthy male volunteers, 18-45 years old, whose physical examinations and semen analyses were normal, were recruited for this study. The maximum diameters of testicular veins during both normal respiration and Valsalva's maneuver were measured by CDS using a 7.5-MHz linear-array transducer. Veins greater than 2 mm in diameter were considered to be a varicocele, and the subjects in these cases were excluded from the analysis. In cases in which reflux was present, the velocity and duration of reflux in the testicular veins during Valsalva's maneuver were measured. Results. Seventy men, whose mean ( standard deviation) age was 27 7 years, were enrolled in this study. Fourteen of the 70 patients had a left varicocele and thus were excluded from the analysis. Of the 112 hemiscrotums in the remaining 56 patients, 61 (54%) had reflux induced by Valsalva's maneuver and 51 (46%) did not. Twenty-two (39%) of refluxes were on the right side, with a mean duration of 1.1 +/- 0.5 seconds, and a mean velocity of 4.2 +/- 2.1 cm/second; 39 (70%) of the refluxes were on the left side, with a mean duration of 1.1 0.5 seconds and a mean velocity of 4.9 +/- 2.3 cm/second. The incidence of reflux was significantly higher on the left side (p = 0.003). The duration and velocity of the reflux did not differ significantly between the right and left sides. The difference in the testicular vein diameters between the right (1.3 +/- 0.2 mm; n = 56) and left (1.6 +/- 0.2 mm; n = 56) sides was statistically significant (p < 0.001). Conclusions. Normal-sized testicular veins in healthy subjects had a remarkably high incidence of reflux induced by Valsalva's maneuver. The presence of reflux in subfertile men with normal testicular vein diameters is a diagnostic criterion, but it is necessary to quantify the reflux to prevent misdiagnosis of a varicocele and unnecessary surgery. The measurement of the duration and velocity limits of reflux in a large series of subjects may provide a reliable indicator for the diagnosis of varicocele. (C) 2002 Wiley Periodicals, Inc.
Keywords: testicular vein; reflux; color duplex ultrasonography; varicocele